Characteristics of graphene-oxide-based flexible and transparent resistive switching memory. (July 2015) - Wu, Hsiao-Yu; Lin, Chun-Chieh; Lin, Chu-Hsuan
Abstract: Recently, resistive switching memory attracts much attention because of its simple structure, easy operation, and non-volatility. In addition, transparent and flexible electronic equipment also attracts much attention. Therefore, ITO/GO/ITO/PES flexible and transparent resistive switching memory devices are proposed. The resistive switching characteristics of the flexible devices are almost unchanged after performing a bending test. So the flexibility of the devices is demonstrated. The retention time of the flexible devices reaches to 10 5 s. The transmittance of the flexible devices is over 80% for the visible light region. Generally speaking, the proposed ITO/GO/ITO/PES device shows great performance. It possibly can be used in the next-generation flexible and transparent electronic equipment.